Identification des raisons de non-fréquentation des centres d’aide en français du postsecondaire au Québec - Isabelle Cabot; Stéphanie Facchin (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
enMastering French (as the first language) for post-secondary students is a major challenge. One solution adopted to address this challenge was the creation of institutional academic skills center (ASC) in French. Since the first ASC created in 1987 (Fortier et Ménard, 2017), they are now well established in 103 higher education institutions in Quebec. Despite that, language proficiency remains globally problematic and, more specifically, teachers report advising students to seek support in French from ASC, but many of them do not attend. Scientific writings about the effectiveness of ASC are poor and even rarer about the use and perception of the mainly concerned users, the students.The exploratory study reported here surveyed post-secondary students to examine the reasons for non-attendance of ASCs. Data were collected through a questionnaire (n = 985) and semi-directed interviews (n = 13). The results show that the organizational reasons, especially concerning time management, are at the top of the list, but reasons of individual order, related to emotion, such as shame or the fear of negative evaluation, would also explain a large part of HC avoidance. In this context, interview participants expressed their ideas for solutions. These results make it possible to propose intervention ideas better adapted to the needs of students, in order to maximize the accessibility and use of HC’s French-language help services.